Targeting Galectins With Glycomimetics - Bertuzzi, Sara; Quintana, Jon I.; Ardá, Ana; Gimeno, Ana; Jiménez-Barbero, Jesús (Frontiers in Chemistry, 2020)
Among glycan-binding proteins, galectins, β-galactoside-binding lectins, exhibit relevant biological roles and are implicated in many diseases such as cancer and inflammation. Their involvement in crucial pathologies makes them interesting targets for drug discovery. In this review, we gather the last approaches towards the specific design of glycomimetics as potential drugs against galectins. Different approaches, either using specific glycomimetic molecules decorated with key functional groups or employing multivalent presentations of lactose and N-acetyllactosamine analogues have provided promising results for binding and modulating different galectins. The review highlights the results obtained with these approximations, from the employment of S-glycosyl compounds to peptidomimetics and multivalent glycopolymers, mostly employed to recognize and/or detect hGal-1 and hGal-3.